Growth and scintillation properties of LiBr/CeBr3 eutectic scintillator for neutron detection. (1st May 2022) - Yajima, Ryuga; Kamada, Kei; Takizawa, Yui; Yoshino, Masao; Kim, Kyoung Jin; Kochurikhin, Vladimir. V.; Yamaji, Akihiro; Kurosawa, Shunsuke; Yokota, Yuui; Sato, Hiroki; Toyoda, Satoshi; Ohashi, Yuji; et al.
Abstract: A 6 LiBr/CeBr3 eutectic thermal-neutron scintillator, with a high 6 Li concentration, was developed using the vertical Bridgman method. The grown eutectic contained an 6 Li molar ratio of 35%, which is higher than those of the commercial neutron scintillators such as Ce:LiCaAlF6 and Ce:Cs2 LiYCl6. Furthermore, it showed optical transparency and a lamellar eutectic structure elongating along the growth direction. The synthesized eutectic showed emission peaks at 360 and 380 nm, originating from the Ce 3+ 5d-4f transition in the CeBr3 scintillation phase. The scintillation performance of 6 LiBr/CeBr3 was evaluated under X-ray, γ -ray, and neutron irradiation to corroborate its neutron detection potential.